Correlation between Self-Efficacy with Activity of Daily Living on Post-Stroke Patients in TMS Clinic RSUD Dr. R. Koesma of Tuban - Noer Innayah; Endah Nurul Kumarijati; Hanim Nur Faizah (International Journal of Multi Discipline Science, 2019)
The Activity of Daily Living (ADL) is important for post-stroke patients. The study aims to identify the correlation of Self-efficacy with ADL on post-stroke patients in TMS Clinic Dr. R. Koesma Hospital of Tuban. Correlative analytic research design with a cross-sectional time approach. The study took a sample of 34 respondents by using Simple Random Sampling. Instrument research used questionnaires. Statistical tests used Spearman Rank. The dependent variable of the study is ADL and the independent variable self-efficacy. The results of the study found that ADL respondents were highly dependent 17.7% were found in respondents with low self-efficacy, independent ADL 23.5% were obtained in respondents with moderate self-efficacy. Data analysis used the Spearman Rank with the significance of α = 0.05. Statistical test results p = 0.03 < α = 0.05 showed there is a correlation between self-efficacy with ADL of patients after stroke. The role of nurses in improving self-efficacy by motivating and providing health education about ADL.